Effect of Learning Behavior and Intellectual Intelligence on Student Accounting Understanding - Blasius Erik Sibarani; Rianto (Jurnal Pendidikan dan Pengajaran, 2022)
Vocational High School students are expected to have the capability to deepen or focus on one field, for example accounting. But in reality students' understanding of accounting is still low, they do not understand the material in the ongoing learning process. That it becomes one of the basic factors that make students unable to take part in learning well. This study aims to analyse the effect of students' intellectual intelligence, and students' learning behavior on accounting understanding. This research uses quantitative research. Primary data is used to obtain basic data with a survey method distributing questionnaires to respondents. The population in this study was 145 people and the sampling in this study used random sampling technique so that the results obtained were 105 students. Classical assumption test used is normality test, multicollinearity test, heteroscedasticity test. Intellectual intelligence is measured by problem solving ability, figure ability, verbal ability and numerical ability. Learning behavior is measured by reading books, attending lessons, studying at home and preparing for exams. For accounting understanding, it is measured by eight concept statements regarding tax accounting, financial accounting, institutional accounting and myob. Based on data processing, the results shows learning behavior has a positive and significant effect on accounting understanding, intellectual intelligence has a positive and significant effect on accounting understanding, and simultaneously intellectual intelligence and learning behavior have a positive and significant effect on accounting understanding.